The Influence of Compensation, Work Environment And Workload on The Performance of Permanent Employees PT Bumi Mandiri Resources - Putri Nur Rodotul Jannah; Maulidyah Amalina Rizqi (INNOVATION RESEARCH JOURNAL, 2024)
The background to this research is that in the last three years employee performance has decreased from 2020-2022. This research aims to test the influence of compensation, work environment and workload on the performance of permanent employees at PT Bumi Mandiri Resources. This research uses quantitative methods. The population in this study was 75 permanent employees, while the sampling used was using non-probability sampling techniques, namely by using sampling. Saturated The reason is because the sample in the study is relatively small, namely less than 100 people, so everyone must be taken from the population. The sample in this study was 75 permanent employees. The analysis technique uses instrument testing, classical assumption testing, and hypothesis testing. For testing tools, use the Statistical Package for the Social Sciences (SPSS). The results of this research show that compensation has a positive and significant effect on performance, the work environment has a positive and significant effect on performance, and workload has a positive and significant effect on performance